2017
DOI: 10.3109/10799893.2014.986743
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between IL-27 rs153109 polymorphism and cancer risk in Chinese population: a meta-analysis

Abstract: IL-27 plays an important role in anti-cancer activity. The -964A/G polymorphism in IL-27 gene has been implicated in susceptibility to cancer, but the results were conflicting. The aim of this study was to assess the association between this polymorphism and cancer risk. Pubmed and Wanfang database were searched for all publications concerning IL-27 -964A/G polymorphism and cancer risk. Odds ratio (OR) and 95% confidence interval (CI) were used to assess the strength of association. Statistical analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…In 2014, Hu et al [ 14 ] conducted a meta-analysis and concluded that IL-27 rs153109 polymorphism was associated with cancer susceptibility in Chinese, whereas the rs17855750 and rs181206 polymorphisms were not. The results were consistent with another meta-analysis conducted by Xu et al [ 15 ], which reported that IL-27 rs153109 polymorphism might enhance cancer susceptibility. Additionally, their results also demonstrated that IL-27 rs153109 polymorphism increased colorectal cancer susceptibility.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In 2014, Hu et al [ 14 ] conducted a meta-analysis and concluded that IL-27 rs153109 polymorphism was associated with cancer susceptibility in Chinese, whereas the rs17855750 and rs181206 polymorphisms were not. The results were consistent with another meta-analysis conducted by Xu et al [ 15 ], which reported that IL-27 rs153109 polymorphism might enhance cancer susceptibility. Additionally, their results also demonstrated that IL-27 rs153109 polymorphism increased colorectal cancer susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…However, the conclusions were inconsistent and inconclusive. In 2014, Hu et al [ 14 ] conducted a meta-analysis of 6 case-control studies and concluded that IL-27 rs153109 polymorphism was associated with cancer susceptibility in Chinese, a result consistent with another meta-analysis of 8 case-control studies by Xu et al [ 15 ] that IL-27- 964A/G (rs153109) polymorphism might enhance cancer susceptibility. Using more recent studies, we conducted an updated meta-analysis to obtain a more precise evaluation of the relevance of IL-27 polymorphisms (rs153109, rs17855750, and rs181206) and cancer susceptibility.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast with our study, a meta-analysis reported that the polymorphism in the IL-27 gene was associated significantly with CRC risk in Chinese population. 32 The difference with our results may be due to ethnic variability in the allelic distribution of Il-27 polymorphism, which suggests that further analyses of the IL-27 genotypes should be performed.…”
Section: Genotypecontrasting
confidence: 95%
“…For example, the association between IL-27p28 (-964 A/G) (rs153109) SNP and susceptibility to asthma and inflammatory bowel disease was found in Korean population (Chae et al, 2007;Li, Zhang et al, 2009). Also, it was suggested that IL-27p28 (-964A/G) polymorphism might enhance cancer risk in Chinese people (Xu et al, 2014).On the other hand, another study did not find any impact for IL-27p28 SNPs on the susceptibility to colorectal cancer (Huang, Wang et al, 2012). The effect of IL-27p28 (-964A/G) on the progression of HBV infection to HCC in Chinese population was examined.No association was found between the presence of this SNP and HCC risk (Peng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%